Study on the Frost Heaving Characteristics and Strength Deterioration of Saturated Red Sandstone Under a Unidirectional Freeze–Thaw Cycle - Zhongyao Li; Qingyang Ren; Zhen Liu; Peiqing Wang; Hao Tang (Applied Sciences, 2025)
In order to explore the influence of the temperature gradient on rock failure degree during freezing and thawing, freeze–thaw-cycle tests were carried out on saturated red sandstone under the conditions of all-directional freeze–thaw and unidirectional freeze–thaw. The results show that the deformation behavior of saturated red sandstone during freeze–thaw cycles is significantly affected by freeze–thaw direction, and the redistribution of water during freeze–thaw cycles leads to significant strain variations. Macro-cracks caused by all-directional freeze–thaw are located in the center of the sample and crack from the inside out, while macro-cracks caused by unidirectional freeze–thaw are perpendicular to the temperature gradient direction and located in the lower part of the sample. Unidirectional freeze–thaw cycles cause the vertical inhomogeneity of the sample to be more obvious, and the uniaxial compressive strength of the sample decreases more significantly in the early stage. After 30 freeze–thaw cycles, the uniaxial strength of all-directional freeze–thaw and unidirectional freeze–thaw samples tends to be stable and virtually identical. The freeze–thaw cycles have seriously damaged the micro-structure of the sample, but the extent of damage to the cementing agents between particles is weaker than that caused by the all-directional freeze–thaw, owing to the seepage path formed in the pore water under unidirectional freeze–thaw conditions.